2017
DOI: 10.1016/j.jbiotec.2017.03.023
|View full text |Cite
|
Sign up to set email alerts
|

Plant tissue cultures as sources of new ene- and ketoreductase activities

Abstract: While many redox enzymes are nowadays available for synthetic applications, the toolbox of ene-reductases is still limited. Consequently, the screening for these enzymes from diverse sources in the search of new biocatalyst suitable for green chemistry approaches is needed. Among 13 plant tissue cultures, Medicago sativa and Tessaria absinthioides calli, as well as Capsicum annuum hairy roots, were selected due to their ability to hydrogenate the CC double bond of the model substrate 2-cyclohexene-1-one. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 41 publications
0
20
0
Order By: Relevance
“…1.3.1.x), which are dependent on flavin mononucleotide. Most of them belong to the "Old Yellow Enzyme" family (OYE) and are involved in the metabolism of fatty acids or in the detoxification process [26]. Although a number of enzymes in this group have been isolated and tested even with the use of microorganisms; in practice, entire cultures are utilized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1.3.1.x), which are dependent on flavin mononucleotide. Most of them belong to the "Old Yellow Enzyme" family (OYE) and are involved in the metabolism of fatty acids or in the detoxification process [26]. Although a number of enzymes in this group have been isolated and tested even with the use of microorganisms; in practice, entire cultures are utilized.…”
Section: Discussionmentioning
confidence: 99%
“…In order to verify the course of the biotransformation over time, a suitable number of flasks with biocatalysts were prepared as described above in the screening procedure. The reactions were terminated after 1,2,3,5,22,23,26,28,45, and 48 h in the case of (4R)-(-)-carvone (1) and after 2, 4, 6, 8, 10, 12, 24, 28, and 48 h for (4S)-(+)-carvone (6).…”
Section: Investigation Of Biotransformation Over Timementioning
confidence: 99%
“…Ene-reductases (ERs) belong to the flavin-containing "Old Yellow Enzyme" family (OYE, EC 1.6.99.1), which includes a class of I flavin-dependent oxidoreductases, which have been extensively studied for their ability to catalyze the asymmetric reduction of electronically activated C=C bonds, possessing electron-withdrawing substituents in the presence of cofactor-recycling systems for NAD(P)H [4][5][6][7][8][9][10][11][12][13][14]. Intracellular ER homologues from bacteria, yeasts, filamentous fungi and higher plants have been isolated and characterized since the 1990s [15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, whole-cells and enzymes catalyzing the C=C hydrogenation and C=O reduction of representative chalcones have been studied for obtaining compounds possessing noteworthy bioactivities. In particular, some dihydrochalcones (achieved via bioreduction of the C=C double bond) have been found to express antioxidant, UV-protective and pro-health activities, which could be interesting for pharmaceutical and cosmetic industries [25,30]. Moreover, their sweet taste make them attractive for producing sweeteners [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…To date, novel ERs have been identied from bacteria, fungi and plants mainly by conventional microbial screening, genome mining and more recently by a protein data bank search guided by catalytic site structural information. 5,[15][16][17] Nextgeneration sequencing technologies and omics approaches have opened up the opportunity to speed up the discovery of useful biocatalysts by providing access to unexplored environmental microbial communities. 18 In a previous study, we have reported a sequence-based functional metagenomics approach to identify novel biocatalysts.…”
Section: Introductionmentioning
confidence: 99%